Проблеми формування архітектоніки управління підприємством на засадах бенчмаркінгу - Стригуль, Лариса Станіславівна; Мелень, Олена Валентинівна; Побережна, Наталія Миколаївна (My University, 2019)
У статті розглянуто особливості формування архітектоніки організаційної структури управління на засадах бенчмаркінгу підприємств України в сучасних умовах господарювання. Необхідність розширення масштабів та підвищення ефективності діяльності вітчизняних підприємств становить нові завдання щодо удосконалення якісного організаційного забезпечення у напрямі формування орієнтирів стабільного довгострокового розвитку, що можливе за наявності визначеної архітектоніки управління підприємством. Одним із найефективніших інструментів, що дає можливість підприємству постійно нарощувати продуктивність, покращувати якість своєї діяльності, бути попереду конкурентів, є бенчмаркінг, який використовується як важіль, здатний зламати усталену структуру організації, що не дає поштовху до розвитку, стиль ведення бізнесу, який не призводить до стрімких проривів в виробництві, та є орієнтиром на кращі результати інших підприємств. Актуальність бенчмаркінгу як методу вдосконалення бізнесу, способу отримання стійких конкурентних позицій на ринку, формування позитивного іміджу базується на багаторічному досвіді успішного розвитку найбільших підприємств і корпорацій у світовій економіці.

The article deals with the peculiarities of the formation of the architectonics of the organizational structure of management on the basis of benchmarking of Ukrainian enterprises in modern economic conditions. The purpose of this research is to substantiate the role of benchmarking in the field of professional development of management personnel and the formation of an effective organizational structure of the enterprise, determining the driving effect on increasing the competitiveness of enterprises from the use of benchmarking in the long term strategic perspective and justification of the peculiarities of the architectural structure of the organizational management of enterprises on the basis of benchmarking, rational directions of growth of their competitor ability. For achievement of the determined purpose and tasks of the research general scientific methods were used: abstract-logical and comparative analysis; comparative analysis; statistical and factor analysis; system structural analysis – in identifying the principles and factors that affect the state; analysis and synthesis – in the substantiation of theoretical and methodical principles of the formation of the enterprise management architectonics. The need to expand the scale and increase the efficiency of domestic enterprises is a new task of improving the quality of organizational support in the direction of forming the benchmarks of stable long-term development, which is possible in the presence of a certain architectonics of enterprise management. In order to maintain a sufficient level of competitiveness for a sustainable development level, any enterprise needs to continuously improve its characteristics. In the current conditions of galloping global competition, even a market leader cannot afford not to work on a strategy of further expansion and / or consolidation in the market. One of the most effective tools that enables an enterprise to continuously increase its productivity, improve the quality of its activities, be ahead of competitors, is benchmarking, which is used as a lever, capable of breaking the established structure of the organization that does not give rise to development, the style of doing business that does not lead to breakthroughs in production, and is a benchmark for the best results of other businesses. Thus, consideration of the problems of forming the architectonics of the organizational structure of enterprise management on the basis of benchmarking is an urgent and urgent issue. Benchmarking can become a tool for in-depth analysis and an effective means of radical change and significant prospects for the development and operation of the enterprise as a whole. The above are currently problems with the introduction of benchmarking by domestic enterprises, but they are all more external. An important part and place in the prospects for implementing the results of benchmarking is the internal unwillingness of the management personnel to change. Actuality of benchmarking as a method of business improvement, a way to get stable competitive positions in the market, the formation of a positive image is based on many years of successful development of the largest enterprises and corporations in the world economy and has great prospects for implementation in the Ukrainian business environment.
Problems of architectonics management by business on benchmarking
Keywords: бенчмаркінг; управління підприємством; оцінювання; архітектоніка; структура організаційна; benchmarking; evaluation; architectonics; enterprise management; organizational structure